LINGUOCULTURAL ASPECTS OF ADDRESS FORMS IN ENGLISH AND GERMAN - Xodjiyeva Nilufar Gʻofur qizi; Sobirova Zebo Bahromovna (TADQIQOTLAR, 2026)
Abstract: The present article examines the linguocultural aspects of address forms in English and German languages. Address forms play an important role in communication because they reflect social relations, cultural norms, and politeness strategies within a speech community. The study focuses on how cultural values influence the choice of address forms in both languages. The research analyzes linguistic units such as titles, pronouns, and honorific expressions that are used to address people in different communicative situations. The findings show that although both languages belong to the Germanic language family, their systems of address forms demonstrate both similarities and differences due to historical development and cultural traditions.